Persophilia Persian culture on the global scene - Dabashi, Hamid 1951- (Harvard University Press, 2015)
"Whence the origin and wherefore the destination of the European and thence global fascination with things Persian? In this book, the author reveals the landscape of a spectacular circulation of ideas between 'East' and 'West' that posits a global scene upon which Persian culture was staged. From the Biblical stories of Esther and Mordechai to Xenophon's Cyropaedia, from Hegel's Philosophy of History to Nietzsche's Thus Spoke Zarathustra, from Mozart's Magic Flute to Handel's Xerxes, from Matthew Arnold's 'Sohrab and Rostam' to Fitzgerald's Rubaiyat of Omar Khayyam, from Montesquieu's Persian Letters and Goethe's West-Östlicher Diwan to Gauguin and Matisse's fascination with Persian paintings, from the rise of the European Enlightenment and Romanticism to the height of American Transcendentalism, Dabashi maps out a geography of European social, intellectual, and artistic history in which Persia and Persian culture were definitive, and which in turn went back to Iran and its Persianate continental context to cause groundbreaking historical changes. The result is an epistemically provocative reading of world history. The book seeks to alter our conception of the European and therefore global fascination with Persian (and by extension Oriental) culture by locating it on the transnational bourgeois public sphere and thus shows it to be definitive to the social and intellectual movements of the eighteenth and nineteenth centuries--from the Enlightenment and Romanticism to the American and French revolutions. In addition, it explores how Persophilia plays a transformative role in the course of postcolonial nation-states, production of a transnational public sphere, and the formation of the postcolonial subject"--Provided by publisher
Includes bibliographical references and index
Distant memories of the Biblical and classical heritage -- Montesquieu, the bourgeois public sphere, and the rise of Persian liberal nationalism -- Sir William Jones, Orientalist philology, and Persian linguistic nationalism -- Goethe, Hegel, Hafez, and company -- From romanticism to pan-Islamism to transcendentalism -- Nietzsche, Hafez, Mozart, Zarathustra, and the making of a Persian Dionysus -- Edward FitzGerald and the rediscovery of Omar Khayyám for Persian nihilism -- Matthew Arnold, philosophical pessimism, and the rise of Iranian epic nationalism -- James Morier, Hajji Baba of Ispahan, and the rise of a proxy public sphere -- Picturing Persia in visual and performing arts -- E.G. Browne, canonization of Persian literature, and the making of a transnational literary public sphere -- Persica spiritualis : Nicholson, Schimmel, Corbin, and their consequences
Keywords: Geschichte; East and West; Orientalism / Europe / History; Social movements / Europe / History; Transnationalism / History; Postcolonialism / History; Civilization; Intellectual life; International relations; Orientalism; Postcolonialism; Public opinion; Social movements; Transnationalism; Internationale Politik; Kulturaustausch; Iran / Civilization; Iran / Foreign public opinion; Iran / Relations / Europe; Europe / Relations / Iran; Europe / Intellectual life; Europe; Iran; Europa